Sustainable Design and Evaluation of Children’s Food Packaging from the Perspective of Buyers’ Preferences - Ying Xiao; Yihan Wang; Yangyang Wei (Foods)
Consumer behavior is one of the key factors influencing product sales, especially in food packaging design, where green, organic, sustainable, and human-centered designs are more effective in promoting food sales. This paper aims to develop a sustainability evaluation method for children’s food packaging. The study first explores the theoretical foundations of sustainability, establishing a systematic set of quantitative indicators and evaluation criteria. Based on this framework, the research gathers consumption behavior, rating data from 250 parents of various ages, professions, and income backgrounds. Using the CRITIC model, the study performs dimensionless processing and detailed quantitative evaluation of the indicators’ comparability, contradictions, and information content to allocate weights for the sustainability evaluation metrics. Furthermore, the MABAC model is applied to construct a weighted decision matrix and boundary approximation area, ranking the sustainability of 20 representative children’s food packaging design schemes (S1–S20). The results show that Scheme S1, after calculation using the CRITIC–MABAC model, has a total distance of 0.214 from the boundary approximation area, exhibiting the smallest deviation from the ideal solution across multiple evaluation criteria and achieving the best overall performance. Building on the optimal Scheme S1, this study comprehensively considers key elements such as eco-friendliness, safety, functionality, and educational value in the optimization of a sustainable design for children’s fruit puree packaging. The research validates the practicality and effectiveness of the quantitative model through the sustainable design and evaluation of children’s food packaging from a consumer behavior perspective, promoting sustainability design and optimization in the children’s food packaging sector.